Understanding Scientology - Henzel, Cynthia Kennedy (Understanding world religions and beliefs., 2019)
Describes the founder, development, core beliefs, practices, and controversies of Scientology. Also discusses the future of the religion. Includes a facts section, color photographs, a glossary, and further resources.